Differential effect of cholesterol depletion on contractile response of the porcine isolated splenic artery - Adamu, Aisha (2021)
The contraction of vascular smooth muscle cells in porcine isolated splenic artery is regulated by signaling pathways on the membrane before generation of any functional response. The vascular smooth muscle cells consist of regions known as caveolae enriched with cholesterol. Cholesterol-rich membrane rafts serve as attachment site on the plasma membrane to different agonist for regulation of responses. In this study, the extraction of cholesterol from membrane by the treatment of different concentrations of methyl-β cyclodextrin (MβCD) i.e. 0.75mM and 3mM. The extraction of cholesterol dissembles the caveolae of vascular smooth muscle membrane. Considering the depletion of cholesterol from vascular smooth muscle cell membrane, the reduced level of cholesterol in the plasma membrane results in change response of phasic contractions of vascular smooth muscle cells of splenic artery to different vasoconstrictor agonist. However, restoration of depleted membrane cholesterol by ingesting cholesterol externally can maintain the normal contractile response of vascular smooth muscle cells. It is now known that signaling pathways for phasic contractions mainly originates from cholesterol enriched membrane domain known as rafts. Our study aims to test the hypothesis that membrane cholesterol depletion results in differing contractile response of different agonist. Methyl-β-cyclodextrin was used as cholesterol acceptor to deplete cholesterol from membrane of vascular smooth muscle cells of splenic artery. The samples of porcine splenic artery were contracted in Krebs-Henseleit solution using organ bath. Transmission electron microscopy was used to examine the disruption of caveolae in the membrane due to treatment of methyl-β-cyclodextrin. The phasic contractions varied as a result of application of different agonists. These agonists act on different receptors present in cholesterol-enriched membrane rafts on the vascular smooth muscle cells of porcine splenic artery. The Phenylephrine and noradrenaline proved to have the same effect both in the absence and presence of membrane cholesterol. The contractile response to endoperoxide analogue U46619 was reduced. The agonist KCl and 5-HT showed decreased vasoconstrictor effect by the treatment of 3mM MβCD. Conversely, the serological data demonstrated that the caveolae were disrupted due to cholesterol depletion in membrane of vascular smooth muscle cells. The results were demonstrated in terms of PD2±SEM of vasoconstrictor effects of different agonist after cholesterol depletion. The ANOVA with post hoc Dunnett’s test was used as statistical interpretation of comparison of control group and treatment group results.